Domestic violence and murder of a transgender women in Russian media: (the case of Anzhela Likina) - Shtorn, Evgeny (Journal of family violence, 2024)
Purpose: This article explores the notion of domestic violence in one of the most media-rich debates around transgender issues in Russia. Anzhela Likina’s murder brought a lot of attention of various outlets from the social media to the federal TV channels. I aim to queer this very notion basing my critique on the case of her murder and the debate that followed afterwards. Methods: I analyse the discourse on family violence as it is given in the publications about the murder of Likina and comments under these publications. I identified 82 media reports on the murder and the following trial. My approach to the reading of these reports, comments and a TV-programme is discourse analysis. Hence, I am looking at power relations which constituted these narratives. Results: In February 2016 Anzhela was stabbed to death by the partner of her ex-wife Gulnara. The murderer built his defence arguing that he killed Anzhela to punish her for beating Gulnara. A detailed look at the media publications reflects that this was a narrative strategy to get a lighter sentence. In turn Anzhela’s mother and sister accused Gulnara of being violent to Anzhela and their two daughters which constitutes another facet of family violence narratives. Based on my analysis of media reports I argue that domestic violence is instrumentalised as a narrative justification for further violence. Conclusions: I uncover the various kinds of violence that Anzhela had to endure on different levels: state violence, societal violence, police violence, domestic violence, and media violence towards her both while she was alive and after her murder. These various kinds of violence amplify one another as the analysis of discourse around them shows.